Cardiovascular pre-participation screening of young competitive athletes for prevention of sudden death in China - Ma, J.; Dai, J.; Sun, B.; Ji, P; Yang, D.; Zhan, J. N. (Journal of Science and Medicine in Sport, 2007)
The cardiovascular pre-participation screening proposal for young competitive athletes has the potential to save young lives. This study aimed to identify individuals at risk for potentially lethal cardiovascular diseases in athletes before competition. Between June 2005 and July 2005, 351 (170 male and 181 female) elite Chinese athletes from 21 sports were profiled. The 12-lead electrocardiogram and echocardiography were employed to evaluate cardiovascular diseases. The vast majority had no definitive evidence of cardiovascular disease. However, abnormal ECGs were identified in 16 athletes (4.5%), including 4 with distinctly abnormal and 12 with mildly abnormal patterns. Only 13 athletes (3.7%) had echocardiographic evidence of relatively mild valve regurgitation that had not been previously suspected. In three athletes with relatively mild ventricular septal hypertrophy (13-14 mm), it was not possible to discern with absolute certainty whether the wall thickening was a manifestation of hypertrophic cardiomyopathy or secondary to athletic conditioning ("athlete heart"). This screening protocol identified no athletes with definite evidence of hypertrophic cardiomyopathy, Marfan's syndrome or other cardiovascular diseases that convey a significant potential risk for sudden death or disease progression during athletic activity. This is largely due to the relative low prevalence of conditions resulting in sudden cardiac death in young athletes and high false positive/negative rates in the tests used as part of the screening process (due to a large overlap between cardiovascular changes due to pathology and those due to intense training).